Scientific activity and life journey the first rector of the Ukrainian Agricultural Academy P.D. Pshenichniy - POLYVACH, Maria (Journal of Education, Technology and Computer Science, 2013)
The article is devoted to an outstanding scientist in zootechnics P.D.Pshenichny, disclosing his life journey and scientific accomplishments.He was a highly educated scientist, investigative experimenter, is closely associatedwith the production, farm workers, was an example of true nationalscholar and active public figure.